Serbian-Slovak ties in the field of musicology through the prism of musicological conferences “Slovak Music in Vojvodina” - Sklabinski, Milina (Napredak, 2026)
The paper is dedicated to the presentation of the scientific and research conferences entitled “Slovak Music in Vojvodina” which have been held in Novi Sad since 2005, i.e., to the Serbian-Slovak ties in the field of musicology as documented in the proceedings of the eponymous conference. The paper maps two main directions. The first refers to the cultural interpenetrations and influences on the conservation and improvement of original folk sons of Slovaks in Vojvodina. The second part presents interesting facts about the activities of Slovak music composers in Serbia. The most important results include the contribution of the musicological conferences during their twenty-year existence and the need to continue these activities in the future period. Namely, this study also shows that Slovak-Serbian ties in the field of musicology have not been sufficiently explored so far.
Keywords: Slovak Music in Vojvodina; Slovak folk songs; Mikuláš Schneider-Trnavský; Viliam Figuš-Bystrý; Martin Kmeć